Analysis of Factors Influencing the Long-term Outcome in Primary Spinal Cord Tumors: Review of Literature - Srinivasan, Uddanapalli; Raghunathan, Natarajan (Indian Journal of Neurosurgery, 2021)
Introduction Primary spinal cord tumors are amenable to total surgical excision but the outcomes are still diverse.Objective The purpose of this study is to identify the significant factors which influence the long-term outcome of spinal cord tumors.Materials and Methods A total of 84 consecutive spinal cord tumor patients who underwent microsurgical excision during April 2003 to 2014 were retrospectively studied. Patients operated after April 2014 were not considered. Ten factors were taken and correlated with the outcome. Multiple regression analysis was used. Patients were periodically evaluated at 1, 6 months, 1, 2, and 5 years. In 72 cases, postoperative MRI scans were performed. The follow-up period ranged between 5 to 15 years.Results In our study, we had 64 extramedullary tumors and 21 intramedullary tumors with varied pathology. Axial location of the tumour (20.294/0.000), extent of the resection of the tumour (13.827/0.001), preoperative Nurick grade (11.349/0.023), and location of the tumour in the spine with respect to vertebral segments (8.151/0.017) were significant predictive factors. We had good outcomes in 65 cases and poor outcomes in 19 cases.Conclusion Our results show location of the tumor with respect to axial plane and vertebral segments were the main contributing factors. They influence the extent of excision of the spinal cord tumor. Preoperative neurological status is the fourth factor which independently determines the long-term outcome. It is one of the few papers where patients have been followed-up for a long period ranging from 5 to 15 years.
Keywords: spinal cord tumors; extramedullary tumor; intramedullary tumor